Economic inequality and subjective well-being across the world - Andrew E. Clark; Conchita D'Ambrosio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We here use repeated cross-section data from the Afrobarometer, Asianbarometer Latinobarometer, and Eurobarometer to analyse the variables that are correlated with both current and future evaluations of standards of living. These are related not only to an individual's own economic resources but also to the country distribution of resources. We consider resource comparisons (the gap in resources between richer and poorer individuals) and the normative evaluation of distribution (conditional on these gaps), given by the Gini coefficient. The "typical" pattern of a negative effect of gaps on the better-off but a positive effect of gaps on the worse-off is found only in Europe: gaps for the better-off in Africa and Central and Latin America have no correlation with current life evaluations and are associated with more positive expectations of the future. Equally, there is no positive estimated coefficient for gaps to the worse-off in Asia. The Gini coefficient is negatively correlated with current life evaluation only in Asia, and is insignificant everywhere else. On the contrary, future life evaluations are more positive in more unequal countries in Africa and Central and Latin America. The relationship between the distribution of resources and measures of individual well-being over time is far from universal.
Keywords: I31; I32; D60; 330; barometers; Gini coefficient; inequality; living conditions; relative deprivation; WIID